2010
DOI: 10.1210/jc.2010-0907
|View full text |Cite
|
Sign up to set email alerts
|

One Year of Growth Hormone Treatment in Adults with Prader-Willi Syndrome Improves Body Composition: Results from a Randomized, Placebo-Controlled Study

Abstract: Unrelated to the GH-IGF-I levels at baseline, our results showed that long-term treatment with GH effectively improved body composition and represents a safe, potential treatment option, relieving some of the negative consequences of PWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(104 citation statements)
references
References 30 publications
5
98
1
Order By: Relevance
“…47 Several studies have documented the safety and efficacy of GH treatment in adults with PWS on body composition and quality of life. 48,49 One study found that the beneficial effects of GH therapy were unrelated to the pretreatment GH or serum IGF-1 levels. 49 Concern about the possible contribution of GH administration to unexpected death has been raised by reported deaths of individuals within a few months of starting GH therapy.…”
Section: Hypogonadismmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Several studies have documented the safety and efficacy of GH treatment in adults with PWS on body composition and quality of life. 48,49 One study found that the beneficial effects of GH therapy were unrelated to the pretreatment GH or serum IGF-1 levels. 49 Concern about the possible contribution of GH administration to unexpected death has been raised by reported deaths of individuals within a few months of starting GH therapy.…”
Section: Hypogonadismmentioning
confidence: 99%
“…48,49 One study found that the beneficial effects of GH therapy were unrelated to the pretreatment GH or serum IGF-1 levels. 49 Concern about the possible contribution of GH administration to unexpected death has been raised by reported deaths of individuals within a few months of starting GH therapy. [50][51][52][53][54][55] The few reported deaths were mostly in obese individuals who had preexisting respiratory or cardiac disorders with evidence of upper airway obstruction and uncorrected tonsillar and adenoidal hypertrophy.…”
Section: Hypogonadismmentioning
confidence: 99%
See 1 more Smart Citation
“…Thigh fat mass and muscle mass were measured in one study. Five studies performed standard 75 g oral glucose tolerance tests (OGTT) [16][17][18][19][20] .…”
Section: Clinical Studies Investigating the Efficacy And Safety Of Rhmentioning
confidence: 99%
“…Changes in exercise capacity in response to rhGH therapy were examined in two studies 17,21) . Sode-Carlsen et al 17) performed a 10-metre walk test and found improvement (faster walking) in 6/18 rhGH-treated patients, but also in 2/16 control patients, and a repeat standing test in which 6/18 rhGH-treated and 4/16 controls had poorer scores compared with baseline.…”
Section: ) Exercise Capacitymentioning
confidence: 99%